The conjuring (California : Warner Bros. Entertainment Inc., 2013)
Based on true events, The Conjuring tells the thrilling story of ghost hunters Lorraine and Ed Warren, who help a family terrorized by an evil spirit in their mysterious farmhouse.
Special feature: Scaring the'@$*%' Out of you.
Based on the true case files of the Warrens.
Director of photography, John R. Leonetti ; music by Joseph Bishara ; edited by Kirk Morri ; executive producers, Walter Hamada, Dave Neustadter.
Vera Farmiga, Patrick Wilson, Ron Livingston, Lili Taylor.
LPF: 18
DVD format, Dual-Layer format, Suitable for all TV screens, Widescreen (2.40:1), Region 3, Dolby Digital.
Keywords: Haunted house films; Horror films; Parapsychology -- Drama